2023
DOI: 10.3389/fpain.2023.1058476
|View full text |Cite
|
Sign up to set email alerts
|

Elucidating factors contributing to disparities in pain-related experiences among adults with or at risk for knee osteoarthritis

Abstract: Background and purposeWe and others have reported ethnic/race group differences in clinical pain, physical function, and experimental pain sensitivity. However, recent research indicates that with consideration for socioenvironmental factors, ethnicity/race differences become less or non-significant. Understanding of factors contributing to pain inequities are needed. Guided by the NIA and NIMHD Health Disparities Research Frameworks, we evaluate the contributions of environmental and behavioral factors on pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 83 publications
0
7
0
Order By: Relevance
“…Imbalances in the representation by different ethnic-race groups from different environmental and sociocultural backgrounds have likely contributed to observed disparities 25 . We and others have shown that with consideration for socioenvironmental factors such as education, income, neighborhood housing status, and experiences of discrimination, previously reported ethnic-race group disparities wane in clinical and experimental pain 26 .…”
Section: Introductionmentioning
confidence: 82%
“…Imbalances in the representation by different ethnic-race groups from different environmental and sociocultural backgrounds have likely contributed to observed disparities 25 . We and others have shown that with consideration for socioenvironmental factors such as education, income, neighborhood housing status, and experiences of discrimination, previously reported ethnic-race group disparities wane in clinical and experimental pain 26 .…”
Section: Introductionmentioning
confidence: 82%
“…In sum, to alleviate the current and future osteoarthritis burden, the interaction of the aging adult's needs, situational, and environmental factors including income and insurance [58][59][60] that can potentiate excess distress and pain, plus health disparities, enormous physical, social, occupational, and mental distresses, must be considered in parallel and intervened upon thoughtfully, comprehensively, in a timely as well as empathetic manner as indicated. However, while this idea is not novel and is consistent with social cognitive theory precepts that are well accepted as explanatory, behavioral and health intervention outcome attributes, unfortunately, this approach is not a mainstream one in any respect.…”
Section: Discussionmentioning
confidence: 99%
“…Results align with the hypothesized interpretation consistent with the allostatic load model, and physiological and neurobiological systems are adaptive to stress until the cumulative load exceeds functional capacity (McEwen, 1998 , 2015 ). Hence, individuals with “combined loads” of high socioenvironmental risk and high chronic pain stage show greater neurobiological “load” as indicated by a pattern of thinner temporal lobe brain structures than their peers with lower levels of socioenvironmental risk and lower levels of chronic pain stage (Mickle et al., 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…Determining the influence of socioenvironmental factors on health outcomes is essential to reducing health disparities and improving health for all. Socioenvironmental factors are associated with chronic pain and brain structure/function (Elbejjani et al., 2017 ; Mickle et al., 2023 ; Peters, 2006 ). Importantly, although socioenvironmental factors were not independently predictive in the adjusted analyses, with the inclusion of an array of socioenvironmental factors, previously observed sociodemographic (ethnic/race) groups, that is, NHB and NHW adults, bilateral temporal lobe cortical thickness differences were no longer observed (Tanner et al., 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation